Synergistic Effects of Steel Fibers and Silica Fume on the Workability, Compressive Strength, and Flexural Strength of Concrete - Kurniawan, Agus; Himawan, Lava (Jurnal Teknik Sipil, 2025)
This study investigates the combined effect of steel fibers and silica fume on the workability, compressive strength, and flexural strength of concrete. Steel fiber content was fixed at 2% by weight of cement, while silica fume was incorporated at varying replacement levels of 0%, 5%, 10%, and 15% of cement weight. Workability was assessed using the slump test, while compressive and flexural strengths were measured at 28 days in accordance with Indonesian National Standards (SNI). The results indicate that silica fume content up to 15% has no significant adverse effect on workability, with all mixtures achieving slump values within the range of 8"“12 cm, classified as good workability. The highest compressive strength was recorded for the 10% silica fume variation at 36.27 MPa, representing a 50.2% increase compared to the control. Flexural strength also peaked at 10% silica fume with a value of 3.97 MPa, corresponding to a 5.2% increase. The improvement in mechanical properties is attributed to the synergistic effect of silica fume"™s pozzolanic reaction and matrix densification combined with the crack-bridging capacity of steel fibers. However, silica fume content above the optimum level resulted in a reduction of mechanical performance, likely due to increased viscosity and microcracking from autogenous shrinkage. The study concludes that a combination of 2% steel fibers and 10% silica fume provides the most balanced enhancement of mechanical performance without compromising workability.